2020
DOI: 10.1523/eneuro.0489-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Connections of Aromatase Circuits in the Medial Amygdala Are Sex Specific

Abstract: The brains of male and female mice are shaped by genetics and hormones during development. The enzyme aromatase helps establish sex differences in social behaviors and in the neural circuits that produce these behaviors. The medial amygdala of mice contains a large population of aromatase neurons and is a critical hub in the social behavior network. Moreover, the neural representation of social stimuli in the medial amygdala displays clear sex differences that track developmental changes in social behaviors. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…In accord with the role of MeA, and aromatase neurons, in sexually dimorphic social behaviors, the MeA displays structural, molecular, and functional sex differences (Nishizuka and Arai, 1981;De Vries et al, 1984;Cooke et al, 1999;Bergan et al, 2014;Billing et al, 2019). In fact, the domestication process of creating isogenic mouse strains may have accentuated sex-differences in circuit function (Chalfin, et al, 2014;Bansal, et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In accord with the role of MeA, and aromatase neurons, in sexually dimorphic social behaviors, the MeA displays structural, molecular, and functional sex differences (Nishizuka and Arai, 1981;De Vries et al, 1984;Cooke et al, 1999;Bergan et al, 2014;Billing et al, 2019). In fact, the domestication process of creating isogenic mouse strains may have accentuated sex-differences in circuit function (Chalfin, et al, 2014;Bansal, et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
“…Because sex differences in the MeA, and specifically in MeA arom+ neurons, are well established (Cooke, et al, 2005;Yao et al, 2017;Billing et al, 2019) we investigated sex differences in synaptic input to MeA arom+ neurons. A regression analysis of the cell counts for all male regions against cell counts for all female regions indicated that the major regions providing synaptic input to MeA arom+ neurons are largely conserved across sexes (Figure 9; R 2 = 0.60252; F = 39.4127; p < 0.00001; linear regression).…”
Section: Sex Differences In Distribution Of Observed Input Cellsmentioning
confidence: 99%
“…On the other hand, aromatase-positive MeA neurons receive afferent projections from the anterior part of the AOB, which relays pheromonal signals from V1R in the VNO. This projection from the AOB to the MeA is sexually dimorphic, much thicker in males than in females [ 126 ], and MeA neurons distribute social, sexual, and predator signals from the AOB to other regions, including the hypothalamic nuclei, in a sex-dependent fashion [ 127 ]. Dopamine receptor D1R-positive neurons in the posteroventral part of the MeA respond to both social and predator signals that mice should approach or avoid, respectively.…”
Section: Regulation Of Opposite-sex Preference By Integrating the Main And Accessory Olfactory Systemsmentioning
confidence: 99%
“…These ionic conductances have been linked to steroidogenesis in these two canonical endocrine organs (Agoston et al, 2004;Hattangady et al, 2016;Kunz et al, 2007a;Traut et al, 2009). For cells that synthesize steroids in the brain, such as neurons that express aromatase (estrogen synthase; Cornil et al, 2004), it is possible that similar intrinsic electrophysiological properties obtain and are distinct from non-aromatase neurons embedded in the same brain regions (Billing et al, 2020). One step toward testing this hypothesis is to examine the response properties of aromatase+ vs aromataseÀ neurons in an identified circuit in which these neurons are known to have significant functions.…”
Section: Introductionmentioning
confidence: 99%
“…Despite an increasing understanding of neuroestrogen synthesis and action in a variety of species and brain areas (Balthazart et al, 2018), the specific activation of aromatase neurons in response to sensory stimuli has not been resolved. Furthermore, aromatase cells have been shown to have specific electrophysiological properties (e.g., aromatase neurons from the amygdala in mice, Billing et al, 2020). Yet despite their central role, the firing phenotype of aromatase neurons within NCM has never been formally studied.…”
Section: Introductionmentioning
confidence: 99%